Effect of murine exposure to gamma rays on the interplay between Th1 and Th2 lymphocytes - Ghazy, Amany A.; Abo-Elnazar, Salma Y.; Ghoneim, Hossam E.; Taha, Abdul-Rahman M.; Abouelella, Amira M. (Frontiers in Pharmacology, 2015)
Background: Gamma radiation or radiotherapy is one of the most widely used treatments for cancer. There is accumulating evidence that adaptive immunity significantly contributes to the efficacy of radiotherapy. Aim: This study is carried out to show the effect of gamma rays on the interplay between Th1/Th2 response, splenocyte lymphoproliferative response to polyclonal mitogenic activators and lymphocytic capacity to produce IL-12 and IL-10 in mice. Methods: mice were exposed to whole body gamma irradiation and tested for the effect of recovery times on splenocyte proliferation and cytokine production. In addition, direct irradiation of spleens and lymphocyte suspension was done. Basal and mitogen-stimulated splenocyte proliferation was assessed by MTT assay while IL-10 and IL-12 were measured using ELISA. Results showed that exposure of intact spleens to different doses of γ-rays (5, 10, 20 gray) caused spontaneous and dose dependent immune stimulation manifested by enhanced cell proliferation and elevated IL-12 production with decreased IL-10 release (i.e. Th1 bias). While exposure of splenocytes suspension to different doses of γ-rays (5, 10, 20 gray) showed activation in splenocytes stimulated by PWM at 5 grays then a state of conventional immune suppression that is characterized by being dose-dependent and is manifested by decreased cell proliferation and IL-12 release accompanied by increase in IL-10 production (i.e. Th2 bias). In addition, we investigated exposure of the whole murine bodies to different doses of γ-rays and found that exposure to low dose γ-rays (0.2 gray) caused a state of immune stimulation terminated by a remarkable tendency for immune suppression. Exposure to 5 or 10 gray of γ-rays resulted in a state of immune stimulation (Th1 bias), but exposure to 20 gray showed a standard state of immune suppression (Th2 bias). Conclusion: Exposure to gamma radiation could cause a state of immune stimulation or suppression via controlling Th1/Th2 cell